Active Design and Characteristic Analysis of Gear Pump with Low Pulsation - Cui Xiangbo; Luo Shanming; Wang Jian (Jixie chuandong)
In order to solve the problem of large flow ripple of gear pumps,an active design method for gear pumps with low flow pulsation is proposed. The basic design thought is to control the shape of the tooth profile by specifying the values of the flow pulsation. The mathematical characterizations of equations for instantaneous flow rate and flow pulsation coefficient are deduced by using the polar distance and the pressure angle function according to gear meshing theory. The mathematical model of the active design of gear pump with low flow pulsation is established,the critical condition of the flow pulsation coefficient is deduced and the design procedure is given. A design for an example gear pump with low flow pulsation is taken to illustrate the proposed method. The characteristics of the gear pump are analyzed. A comparison study of the above characteristics of the involute gear pump is also carried out. It is significant to reduce the flow pulsation,improve the working stability and extend the service life of gear pumps.